The New Arab Revolutions that Shook the World - Khosrokhavar, Farhad (Boulder, London Paradigm Publishers, 2012)
Long considered overwhelmingly resilient, Arab authoritarian regimes have begun to fall in surprising manner. While the future of governance in these countries is unclear, the new Arab movements, largely secular and youthful, reveal a vital and ambitious new Arab generation. For these youth, radical Islam has lost its seductive appeal and religion is being marginalized. Women now are far more visibly active in
Inslude Glossary, Notes and Bibliography
History
Keywords: Democratization -- Arab countries -- History -- 21st century. -- Protest movements -- Arab countries -- History -- 21st century. -- Youth protest movements -- Arab countries -- History -- 21st century..